Quantics Tensor Cross Interpolation for High-Resolution Parsimonious Representations of Multivariate Functions - Ritter, Marc K.; Núñez Fernández, Yuriel; Wallerberger, Markus; von Delft, Jan; Shinaoka, Hiroshi; Waintal, Xavier (Physical review letters, 2024)
Multivariate functions of continuous variables arise in countless branches of science. Numerical computations with such functions typically involve a compromise between two contrary desiderata: accurate resolution of the functional dependence, versus parsimonious memory usage. Recently, two promising strategies have emerged for satisfying both requirements: (i) The quantics representation, which expresses functions as multi-index tensors, with each index representing one bit of a binary encoding of one of the variables; and (ii) tensor cross interpolation (TCI), which, if applicable, yields parsimonious interpolations for multi-index tensors. Here, we present a strategy, quantics TCI, which combines the advantages of both schemes. We illustrate its potential with an application from condensed matter physics: the computation of Brillouin zone integrals.